Reconstructing Children's Character Formation Through Qur’anic and Moral Education: Insights from Contemporary Kuttab Practices - Hanifah Wafa Firdaus; Eric Salonen (Walidem Institute and Publishing (WIP), 2025)
Objective: This study aims to examine the role of Kuttab in shaping children's character through Qur'an and moral education, with a case study in Kuttab Karanganyar. The background of this research is based on the urgent need for a character education system rooted in Islamic values, as a response to the moral and ethical crisis that has hit the younger generation. Kuttab, as a traditional Islamic educational institution, offers a holistic approach to early childhood education, especially through strengthening Islamic values from an early age. Theoretical framework: This study refers to the theory of character formation according to Thomas Lickona, which emphasizes the aspects of moral knowing, moral feeling, and moral action, as well as Islamic education theory, which emphasizes the integration between faith, knowledge, and charity. Literature review: shows that Qur'anic education and morals are important foundations in shaping children's personalities with noble character. Methods: The research used was a descriptive qualitative approach with case studies. Data was collected through observations, in-depth interviews, and documentation of educators, parents, and students in Kuttab Karanganyar. Data analysis was carried out thematically. Results: research shows that Kuttab Karanganyar has succeeded in shaping children's character through habituation of memorizing the Qur'an, learning meaning and manners, and example from the ustadz. Character building is carried out systematically and continuously, with the support of a conducive environment and the active involvement of parents. Implications: This study shows that the Kuttab education model can be used as an alternative in the development of Islamic-based character education. Kuttab's advantage lies in the integration between the spiritual and moral curriculum with methods that touch the child's heart. Novelty: from this study is the disclosure of the mechanism of character formation in Kuttab systematically and contextually in the modern era, which has not been widely discussed in academic studies.